Documentary sources to create trust among digital users: Proposals from media - Marcos Recio, Juan Carlos (2019)
The media have taken more than two centuries to achieve their reputation. As if by magic it has disappeared from the media sphere and the editors do not find a solution. Guilty? The media itself that did not know how to adapt to the new environments, the social networks that passed without compassion like a roller and, the users, readers, listeners, etc., who bet on the speed and simplicity of the information offered by the social networks. And this was 2016. The year in which political communication changed the value of information and its relationship with the media, based on the proposals of President Donald Trump. Since then, a flood of false information, produced ah doc by “mercenaries” content, amplified in social networks and aired through the print media, have brought a new order in communication. This article analyzes the current situation with reference to the Fake News and the post-truth society, in which the media is adapting and using technology to reorganize information. A followup is made to different organizations and institutions that are showing auspicious results to avoid misinformation and bad practices. Finally, from sources of information, tools and recommendations are offered so that journalists establish an order of priorities and adjust to the data to create an information in accordance with truth and social justice.